1994
DOI: 10.1046/j.1471-4159.1994.63020596.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Elevations of Glucocorticoids Potentiate Glutamate Accumulation in the Hippocampus

Abstract: Glucocorticoids (GCs) are secreted during stress and can damage the hippocampus over the course of aging and impair the capacity of hippocampal neurons to survive excitotoxic insults. Using microdialysis, we have previously observed that GCs augment the extracellular accumulation of glutamate and aspartate in the hippocampus following kainic acid‐induced seizures. In that study, adrenalectomized rats maintained on minimal GC concentrations were compared with those exposed to GCs elevated to near‐pharmacologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
0
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(80 citation statements)
references
References 40 publications
8
70
0
2
Order By: Relevance
“…Elevation of these proinflammatory factors is accompanied with dendritic atrophy and neuronal death within the hippocampus, 161,162 which are also found in brains of subjects with MD. These detrimental effects of glucocorticoids in the CNS are mediated by a rise in extracellular glutamate 163,164 and subsequent overstimulation of the NMDA receptor. Such an overstimulation of the NMDA receptor results in excitotoxic neuronal damage.…”
Section: Stress and Cns Immune Systemmentioning
confidence: 99%
“…Elevation of these proinflammatory factors is accompanied with dendritic atrophy and neuronal death within the hippocampus, 161,162 which are also found in brains of subjects with MD. These detrimental effects of glucocorticoids in the CNS are mediated by a rise in extracellular glutamate 163,164 and subsequent overstimulation of the NMDA receptor. Such an overstimulation of the NMDA receptor results in excitotoxic neuronal damage.…”
Section: Stress and Cns Immune Systemmentioning
confidence: 99%
“…Furthermore, the increases in extracellular GLU in various brain areas after exposure to acute or chronic stressors (Broom and Yamamoto, 2005;Lowy et al, 1995;Moghaddam, 1993) are attenuated by adrenalectomy (Lowy et al, 1993;Moghaddam et al, 1994). Moreover, elevations in glucocorticoids or psychological stress exacerbate the increase in extracellular GLU, neuron loss, and spectrin proteolysis in the hippocampus produced by kainic acid (Stein-Behrens et al, 1992, 1994b.…”
Section: Introductionmentioning
confidence: 99%
“…Transient global ischemia increases proliferation in the SGL by 12-fold between 6 and 11 days after surgery. There is a threefold increase in the number of new neurons 28 days after the last BrdU injection [18]. Interestingly, it has been shown that some of the effects of ischemia on the brain may mediated by NMDA and AMPA receptors [40,41].…”
Section: Regulation Of Adult Neurogenesismentioning
confidence: 99%
“…As reviewed above, proliferation and neuronal recruitment in the adult dentate gyrus can be altered by adrenal steroids [15,28], the blockade of NMDA receptors [33], estrogen [19], seizures [17,20], ischemia [18], serotonin [23], opiate [24] and lithium administration [25]. Although all these treatments probably have different modes of action, they may all result in changes in granule neuron activity and/or their extracellular microenvironment within the GCL, which in turn may alter the proliferation of neuronal precursors in the SGL.…”
Section: Radial Regulation Of Adult Neurogenesis; a Hypothesismentioning
confidence: 99%
See 1 more Smart Citation